Progestogen Profiling Over the Course of Diapause and Resumption of Embryo Development in the European Roe Deer - Vera A. van der Weijden; Anna-Katharina Hankele; Anna B. Rüegg; Marion Schmicke; Karoline Rehm; Laurent Bigler; Susanne E. Ulbrich (Ital Publication, 2019)
Progesterone (P4) plays a pivotal role in maintenance of pregnancy in many mammalian species. Species-specific P4 metabolites have been shown to function as primary acting progestogen and the receptor binding capacity varies between species. The European roe deer (Capreolus capreolus) displays a 4-5 month period of embryonic diapause, which decouples fertilization from implantation. The majority of roe deer have two corpora lutea that secrete P4. No changes in P4 concentrations have been observed during pre-implantation embryo development. As 5α-DHP is known to play a major role during pregnancy in elephants and horses, we hypothesized that 5α-DHP functions as additional progestogen facilitating embryo reactivation. The profile of 11 progestogens was quantified in roe deer plasma over the course of diapause and resumption of embryo development including P4, 3α- and 3β-DHP, 20α- and 20β-DHP, 5α- and 5β-DHP, 3α,5α- and 3α,5β-THP, as well as 3β,5α- and 3β,5β-THP. While P4 was most abundant during diapause and resumption of development, 20α-DHP was the most abundant P4 metabolite. This is different than in pregnant elephants, where 5α-DHP was most abundant, and the luteal phase in cattle, where 3α,5α-THP was most abundant. With the exception of a weak correlation of 3β,5α-THP, none of the progestogens significantly correlated with embryonic development in the roe deer. Thus, plasma 5α-DHP does not seem to play a role in embryo reactivation. We propose that progestogens might contribute to priming the endometrium for supporting embryo development and preparation for implantation.